2008
DOI: 10.1590/s0100-06832008000100005
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e desenvolvimento do amaranto (amaranthus spp.) sob estresse salino e cobertura morta

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
0
3
0
11
Order By: Relevance
“…It can also be observed that, at 100 mM of NaCl, the estimated contents of Cl -and Na + were 0.91 mmol g -1 and 1.26 mmol g -1 of dry mass in the leaves, 1.26 mmol g -1 and 2.43 mmol g -1 of dry mass in the stem and 0.64 mmol g -1 and 2.38 mmol g -1 of dry mass in the roots, respectively ( Figures 4A, 4B, 4C, 4D, 4E and 4F). Costa et al (2008) also observed that salinity increased the Cl -and Na + contents in different parts of Amaranthus ssp.…”
Section: Resultsmentioning
confidence: 76%
“…It can also be observed that, at 100 mM of NaCl, the estimated contents of Cl -and Na + were 0.91 mmol g -1 and 1.26 mmol g -1 of dry mass in the leaves, 1.26 mmol g -1 and 2.43 mmol g -1 of dry mass in the stem and 0.64 mmol g -1 and 2.38 mmol g -1 of dry mass in the roots, respectively ( Figures 4A, 4B, 4C, 4D, 4E and 4F). Costa et al (2008) also observed that salinity increased the Cl -and Na + contents in different parts of Amaranthus ssp.…”
Section: Resultsmentioning
confidence: 76%
“…A redução nos totais extraídos de Na observados no presente estudo diverge dos resultados obtidos por Costa et al (2008) no amaranto, em condições de casa de vegetação, por Neves et al (2009), estudando a mesma cultivar do feijão-Tabela 3. Totais extraídos de Na, K, P e Ca, em g vaso -1…”
Section: Teores E Conteúdos De Elementos Minerais Na Plantaunclassified
“…Já Costa et al (2008), com amaranto, constataram tolerância à salinidade da água de irrigação até o limite de 4,5 dS m -1 , devido à não verificação de efeito sobre a massa de matéria seca total.…”
Section: Massa De Matéria Seca Da Parte Aérea E De Raizunclassified